AN INVESTIGATION OF VISUAL PERCEPTION LEVELS OF PRESCHOOL CHILDREN IN TERMS OF DIFFERENT VARIABLES - (:unkn) unknown (My University, 2019)
Pre-school ages, which is the period of rapid development of all developmental areas, is thestage in which children acquire visual perception ability and this ability acquisition processaccelerates between the ages of three and seven. Visual perception that accelerates duringchildhood, is an important factor for academic and motor skills which are essential for schoolsuccess. In this research, it is aimed to examine visual perception levels of preschool childrenaccording to various variables. The research was conducted through the survey model. Thestudy population is consisted of children aged 5-6, who are attending preschools affiliated tothe Ministry of National Education in Kadıköy, Maltepe, Beşiktaş and Sarıyer districts onAnatolian and European sides of Istanbul. The sample of the study consists of 114 childrenaged between 5-6 years and who study in preschools affiliated to the Ministry of NationalEducation in these districts. The "Visual Perception Scale for Preschool Period" and personalinformation form were used to collect data for the study. Data were analyzed with MannWhitney U test and Kruskal Wallis one-way analysis of variance. According to the results ofthe findings, while preschool children's visual perception levels do not differ according to thegender, age and duration of education variables; there is a significant difference in favor ofhigh-middle socio-economic level based on the socio-economic level variable. The findingsare discussed in the framework of the relevant literature.
Keywords: Eğitim, Eğitim Araştırmaları